Long-term dental stability after orthognathic surgery: a systematic review. (9th September 2020) - Mulier, Delphine; Gaitán Romero, Lesly; Führer, Alberto; Martin, Catalina; Shujaat, Sohaib; Shaheen, Eman; Politis, Constantinus; Jacobs, Reinhilde
Summary: Background: Long-term dental stability is one of the main objectives following combined orthodontic and orthognathic surgical treatment. It is influenced by multiple factors such as surgical, patient-related, and orthodontic aspects. While recent reviews mainly focus on short-term dental changes (0.5–2 years), longer follow-up dental stability remains hardly reviewed. Objectives: The aim of this study was to evaluate long-term stability of dental and dentolabial changes following combined orthodontic and orthognathic surgical treatment with a minimum follow-up period of 5 years. Search methods: A systematic search was conducted up to December 2019 using Pubmed, Embase, Web of Science, and Cochrane Central. Selection criteria: Randomized controlled trials (RCTs), prospective and retrospective cohort studies, and case series with a minimum of 10 patients, which reported long-term dental stability following combined orthodontic and orthognathic treatment, were included. Data collection and analysis: Long-term changes were assessed for overjet, overbite, maxillary, and mandibular incisors' position and relationship of lip position to maxillary and mandibular incisors. Risk of bias was assessed according to the Cochrane Handbook. Results: Following the screening of 3178 articles, 11 studies were included (2 RCT, 9 retrospective) with a postoperative follow-up period ranging from 5 to 15 years. A decrease in overjet was observed for patients with skeletal class III malocclusion, whereas overjet increased in class II patients at long-term follow-up. Overbite increased in class II patients, whereas class III showed variable results. The lower incisor position was more stable vertically than horizontally; the latter showing more outcome variability. Dentolabial changes corresponded to the normal ageing process and results were not clinically significant after long-term follow-up. Conclusion: Current evidence suggests variability of dental and dentolabial stability in both skeletal class II and III patients. Further prospective studies are required to develop guidelines for long-term follow-up assessment using computer tomography or cone-beam computed tomography imaging, before final conclusions can be drawn. Registration: The protocol for this systematic review (CRD42020133844) was registered in the International Prospective Register of Systematic Reviews (PROSPERO).